Animal models of lupus nephritis: the past, present and a future outlook - Katikaneni, Divya; Morel, Laurence; Scindia, Yogesh (Autoimmunity (Chur, Switzerland), 2024)
Lupus nephritis (LN) is the most severe end-organ pathology in Systemic Lupus Erythematosus (SLE). Research has enhanced our understanding of immune effectors and inflammatory pathways in LN. However, even with the best available therapy, the rate of complete remission for proliferative LN remains below 50%. A deeper understanding of the resistance or susceptibility of renal cells to injury during the progression of SLE is critical for identifying new targets and developing effective long-term therapies. The complex and heterogeneous nature of LN, combined with the limitations of clinical research, make it challenging to investigate the aetiology of this disease directly in patients. Hence, multiple murine models resembling SLE-driven nephritis are utilised to dissect LN's cellular and genetic mechanisms, identify therapeutic targets, and screen novel compounds. This review discusses commonly used spontaneous and inducible mouse models that have provided insights into pathogenic mechanisms and long-term maintenance therapies in LN.